Pencabutan Gigi yang Irrasional Mempercepat Penurunan Struktur Anatomis dan Fungsi Tulang Alveolar - Zahreni Hamzah; Nadia Kartikasari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2015)
Tooth extraction is the most common dental treatment procedure in Indonesia. This is happened due to lack of knowledge and awareness of the effect of tooth extraction. Many patients requested dental extraction for some reason such as do not stand the pain anymore, dental treatment is expensive and long, althought the fact that such cases can still be treated. This condition called irrational extraction. Irrational extraction may cause loss of important componets for bone regeneration such as periodontal ligament stem cells/PDLSC, dental pulp stem cells/DPSC, extracellular matrix/ECM and local growth factor. PDLSC has potential differentiation into osteoblast, fibroblast periodontal ligament, and sementoblast. DPSC induces odontontoblast to form reparative dentin. Local growth factors are important component for hard and soft tissue regeneration. Due to loss of important component for bone regeneration, bone became small, thin, and brittle, which allows bone fracture. The purpose of this review is to explain the effect of irrational extraction on mesenchymal stem cell, periodontal ligament, ECM, and local growth factor. This knowledge is expected to reduce irrational tooth extraction.